A smart transformer application for voltage controlled home energy management system - Selamogullari, Ugur S.; Elma, Onur (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2018)
Today, more efficient use of electrical energy requires that the demand on the customer side must be controlled through demand response applications. Smart grid structure provides a way to the widespread use of demand response applications at the customer side. Smart homes can be considered as the sub-unit of the smart grid and there are several studies on home energy management applications for more efficient and more controlled electrical energy use in these homes. In this study, a smart transformer design for voltage controlled home energy management system is given. The power consumption of the house can dynamically be controlled by integrating the smart transformer to the new home energy management system so that the voltage level at the home entrance can be reduced based on a signal from the home energy management system. If this does not provide enough power reduction, then load shifting/load shedding together with the voltage control is implemented to further reduce the power consumption of the house. The developed smart transformer is experimentally validated at YTU Smart Home Laboratory and it is seen that about %30 peak load reduction can be obtained using both voltage control and load shifting together.
Keywords: Home energy management; Smart transformer demand response; conservation voltage reduction; smart home; DEMAND-SIDE MANAGEMENT; REDUCTION; ALGORITHM; Engineering